THE GEODETIC BASIS FOR CREATING THEMATIC MAPS OF THE POPULATION AND TRADITIONAL AND MODERN METHODS OF DRAWING UP CARDS (American Journal of Technology and Applied Sciences, 2023)
In this article, the use of the knowledge base as well as the database for the creation of electronic dynamic cards of the population of Fergana region, and the study of types that have not been well studied so far, the acceptance of data in the case of establishing a geodetic basis, this issue is urgent. one of the issues, and researchers in recent years have taken not only the improvement of electronic card creation technology, but also prevention of "bad" card creation as the main goal.